The effect of using the generative learning model on the achievement of biological concepts among the first intermediate grade students (Journal of the College of Basic Education, 2022)
The current research aims to identify the effect of using the generative learning model on the achievement of biological concepts among the first intermediate grade students, and for the purpose of verifying the aim of the research, the following null hypothesis was formulated: